ONTOGENICAL OBSTACLE PESERTA DIDIK DALAM MEMPELAJARI HUBUNGAN ANTAR SUDUT SALING BERPENYIKU KELAS VII SMP - Ayathollah Khomeni; Yuni Rhamayanti (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
Abstract Mathematics consists of several sections of science concentration, one of which is geometry. Lines and angles are the most basic geometric material studied by students at the Junior High School (SMP) level in class VII. Lines and angles are basic material that is very important for students to understand as a basis for understanding subsequent geometry material. Ontogenic obstacles (ontegic obstacles) are one of the obstacles related to students' mental readiness in terms of the limited knowledge possessed by students, both in terms of application context and in terms of cognitive maturity in accepting new knowledge. The aim of the research is to analyze the types of ontogenic obstacles identified by students in learning the material about lines and angles in the sub-discussion of angles. The method used in this research is a qualitative method with a Didactical Design Research model approach through retrospective analysis. Data collection in research applies triangulation techniques, namely through observation, documentation and interviews. The results of this research indicate that students experience learning obstacles of the ontogenic type in learning the relationship between angles at angles school in line and angle material class VII SMP.